Corporate leniency programs for antitrust: Past, present, and future - Jeroen Hinloopen; Sander Onderstal; Adriaan R. Soetevent (Tinbergen Institute, 2023)
This special issue marks the 25th anniversary of the introduction of a leniency program for antitrust in the EU and contains five original papers: Each paper examines the effects of design parameters of leniency programs on their performance. Before introducing each contribution separately, we put them in perspective by introducing readers to the existing theoretical, empirical, and experimental literature on corporate leniency programs for antitrust.
Keywords: L41; L44; 330; Leniency programs; antitrust; competition policy; cartel